Pelatihan Alat Peraga Jam Sudut Pada Guru di SD YPK Kwadeware, Jayapura - Sukmawati Sukmawati (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2023)
Pedagogic competence as one of the competencies that must be owned by teachers needs to be constantly improved so that skills in managing classes become better. One of the efforts made is to take part in training on the use of visual aids as a bridge in delivering teaching materials. At the elementary school level, mathematics material requires learning media in the form of visual aids so that students are able to understand real mathematical concepts through concrete objects in the form of visual aids. The fact is that in the field the use of learning media is only for some basic material that is understood, so it is necessary to hold training on the use of mathematical teaching aids. This service activity aims to improve teacher skills in using learning media in the form of a corner clock teaching aid which is carried out in several stages, including preparation, implementation of training, and evaluation. After participating in this training, it can be concluded that the trainees understand and are skilled in using corner clock teaching aids and are highly motivated to develop their skills in using teaching aids in mathematics learning activities in class.